The Influence Of Legal Profession Interest On Teens Through Netflix Viewing In Indonesia - Putri Sonya, Assyfa; Suherman, Suherman; White , Alan Robert (CV. Era Digital Nusantara, 2024)
This study aims to determine the extent of the influence of using the Netflix application on the interest levels of teenagers in Indonesia with regard to working in the field of law. Given the development of science, technology, and information due to globalization that cannot be stopped in the world, including in Indonesia, it has resulted in anyone being able to easily access various things via the Internet, including just for entertainment. It is not surprising that currently teenagers in Indonesia access a lot of watch-on-demand applications, especially Netflix. The many choices of films that can be easily accessed by teenagers make them fond of watching Netflix to find entertainment, including films that have legal themes/elements or are related to the world of law. Considering that adolescence is a time of searching for identity or self-identity, which makes teenagers vulnerable to interference or influence, whether in the form of ideas, feelings, behavior, intellectual capacity, or new dreams to be achieved. Therefore, at this age/phase of adolescence, teenagers generally begin to determine the direction and attitude related to their profession in the future. Of course, teenagers in determining their professional interests are influenced by various factors, one of which is the influence of shows accessed by teenagers on Netflix.